2014
DOI: 10.1093/rb/rbu007
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the surface modification techniques of bone-related implants for last 10 years

Abstract: At the time of implanting bone-related implants into human body, a variety of biological responses to the material surface occur with respect to surface chemistry and physical state. The commonly used biomaterials (e.g. titanium and its alloy, Co–Cr alloy, stainless steel, polyetheretherketone, ultra-high molecular weight polyethylene and various calcium phosphates) have many drawbacks such as lack of biocompatibility and improper mechanical properties. As surface modification is very promising technology to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 184 publications
0
59
0
Order By: Relevance
“…Compared with other coating methods, the advantages of ion beam surface modification are that this technique avoids the risk of delamination and that the process is extremely controllable and reproducible [100]. Improvement of the tribological behaviour, as well as the surface mechanical properties of polymeric materials, was reported in [101] and surface wear reduction was found on UHMWPE by using nitrogen ion implantation [102,103]. It is believed that this surface modification method has hardening and stiffening effects.…”
Section: Ion Beam Surface Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other coating methods, the advantages of ion beam surface modification are that this technique avoids the risk of delamination and that the process is extremely controllable and reproducible [100]. Improvement of the tribological behaviour, as well as the surface mechanical properties of polymeric materials, was reported in [101] and surface wear reduction was found on UHMWPE by using nitrogen ion implantation [102,103]. It is believed that this surface modification method has hardening and stiffening effects.…”
Section: Ion Beam Surface Modificationmentioning
confidence: 99%
“…The process involves coating, etching and transferring a photo-resist layer to the surface of a bulk material whose surface properties need to be improved [103]. In the study conducted in [107], photolithograpy was used to generate dimples with a diameter of 50 μm, a depth of 15 μm and the area density in a range of 5% to 40% on both stainless steel and UHMWPE surfaces.…”
Section: Photolithography and Nanoimprint Lithographymentioning
confidence: 99%
“…Especially for cementless TJR implants, the biological response to the surface chemistry and physical state is crucial for the success of implant integration as it depends on sufficient primary anchorage and biological fixation by newly formed bone (Anselme, Ponche, & Bigerelle, ; Kienapfel, Sprey, Wilke, & Griss, ; Ponche, Bigerelle, & Anselme, ). Therefore, many surface modification techniques have been developed including coating, roughening, and patterning methods (Qiu, Chen, Wang, & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
“…IBD can be divided in two subcategories: ion beam induced deposition (IBID) and ion beam sputtering deposition (IBSD). Conversely, ion beam assisted deposition (IBAD) technique offers a better solution to create gradual transition layer mixed with substrate material and the depositing material at the interface between them compared to IBD, wherein coating adheres with relatively lower adhesive strength onto the substrate . For instance, Chen et al reported the preparation of calcium phosphate thin film coatings on pure titanium using IBAD and further created biomimetic apatite precipitation layers via immersing the coating in Dulbecco's phosphate buffered saline solutions containing calcium chloride, as well as biomolecules to modulate precipitation processes and enhance its bioactivity …”
Section: Physical Approachmentioning
confidence: 99%